Butterfly fauna (Lepidoptera: Rhopalocera) of Donji Emovci, Požega, Croatia - Toni Koren; Goran Letić (Natura Sloveniae)
An example of a photographic faunistic study of butterflies implemented in Croatia is presented herewith. The survey was conducted in the near surroundings of Donji Emovci village, near Požega, Slavonia, between 2009 and 2013. The surveyed area consists mostly of a mosaic of different kinds of monocultures, scattered grasslands and forest fragments. Seventy-nine butterfly species could have been reliably identified from the photographs, several of which are rare or interesting records for Croatia (e.g. Colias erate, Parnassius mnemosyne and Cupido decoloratus). This study shows that butterfly photography can indeed be a useful tool for faunistic studies, although additional methods should be used to gain complete species lists.